Critical factors influencing the bid or no-bid decision of the indigenous small building contractors in Tanzania. Issue 2 (27th June 2020) - Chileshe, Nicholas; Kavishe, Neema; Edwards, David John
Abstract : Purpose: This study aims to investigate and ranks the critical factors influencing the bid or no-bid decision and their importance for the indigenous small building contractors within the Tanzanian construction industry. Design/methodology/approach: An interpretivist epistemological design was adopted to extensively manually review and search extant literature on bid or no-bid decision-making criteria. A total of 30 most common bid or no-bid decision-making criteria were identified. These were included in a questionnaire survey data collection instrument. The survey was distributed to 40 small indigenous (local) building contractors in Dar es Salaam, Tanzania. In total, 33 responses were received. Response data was subjected to both descriptive and inferential statistics. Findings: The results show a disparity of ranking of the 30 bid/no-bid criteria factors among the two grades of small contractors, with 11 factors having statistically significant differences ( p = < 0.05). Based on the overall sample, the most highly ranked seven factors in ascending order were: availability of capital; financial capacity of the client; project size; profitability; project type; need of work; and current workload. The following were the least ranked: tax liability; the degree of safety; availability of other projects; availability of labor; bidding document price; and uncertainty because of weather conditions. Availability of capital and financial capacity of the client were jointly ranked as the most important by Class VI contractors. In comparison, availability of capital and need of study were rated highly for Class VII contractors. Research limitations/implications: The sample consisted of indigenous small building contractors in one industry operating in Tanzania only and did not include the perceptions of the foreign contractors based in Dar es Salaam. Future studies are required to expand the current research and investigate this specific aspect further. Practical implications: The identified "bid/no-bid criteria" information will allow indigenous small building contractors to enhance the efficiency and effectiveness of their bidding decision-making process. Emergent findings will enable said contractors to: better fit into the competitive construction business environment; increase their awareness of existing decision-making practices; and develop appropriate strategies for evaluation of opportunities encountered. Cumulatively, these findings benefit small indigenous building contractors by increasing their understanding of the factors influencing bid decision. Originality/value: The study represents the first empirical study in Tanzania on the critical factors influencing the bid or no-bid decision among the indigenous small building contractors, which face fierce competition from foreign contractors.